Increased risk of gestational vascular complications in women with low free tissue factor pathway inhibitor plasma levels out of pregnancy - Ittel, Antoine; Bretelle, Florence; Gris, Jean-Christophe; Chau, Cécile; Sébahoun, Gérard; Boubli, Léon; Arnoux, Dominique (Thrombosis and Haemostasis, 2011)
Tissue factor pathway inhibitor (TFPI) plays a crucial role in haemostasis by regulating TF-induced initiation of coagulation. Since it is expressed by endothelial and trophoblastic cells, TFPI is of particular importance at the placental level and might be involved in the occurrence of gestational vascular complications (GVC). In the present study, we investigated plasma free TFPI antigen in four groups of women: healthy non-pregnant women without history of pregnancy complications; women at the beginning (<12 weeks) and women during the third trimester of a normal pregnancy; women with late pregnancy complications (pre-eclampsia / HELLP syndrome, intra-uterine fetal death, fetal growth retardation) at the time of obstetrical event and/or at distance from pregnancy. In normal pregnancy, TFPI increased between first trimester and delivery (median 5.0 ng/ml vs. 7.1 ng/ml; p<0.0001) but remained lower than in non-pregnant controls (median 8.2 ng/ml; p<0.0001). In patients, when measured concomitantly to the obstetrical event, TFPI showed no difference with normal late pregnancy levels. In contrast, at distance from pregnancy, in the absence of any hormonal influence, TFPI was significantly lower than in non-pregnant controls (median 5.9 vs. 8.2ng/ml, p < 0.0001). After categorisation into quartiles, an inverse dose-effect relationship was demonstrated between TFPI categories recorded apart from pregnancy and GVC risk, with a crude odds ratio of 43.5 (95% confidence interval 8.2–230) for patients with TFPI values in the lowest quartile (< 5.7 ng/ml). In conclusion, low free TFPI at distance from pregnancy appears to be a strong indicator of GVC risk.
Keywords: Tissue factor pathway inhibitor (TFPI); coagulation inhibitors; pregnancy; gestational vascular complication